ENHANCING EMPLOYEE PERFORMANCE THROUGH DIGITAL TRANSFORMATION, COMPETENCE, AND AGILITY: THE ROLE OF STRATEGIC LEADERSHIP AS A MODERATOR - Subariyanti, Herudini; Yulianto, Andri Rizko; Rifandi, Yandri Ahmad; Punamasari, Dina (Dynamic Management Journal, 2025)
This study aims to conceptually examine the contributions of digital transformation, digital competence, and organizational agility in enhancing employee performance, with strategic leadership as a moderating variable. The conceptual model was developed through a literature review of scholarly articles from SINTA, Google Scholar, and Scopus databases published between 2018 and 2024. The findings indicate that digital transformation and digital competence influence organizational agility and organizational agility enhances organizational adaptability to change. Furthermore, strategic leadership amplifies the effects of these three factors on employee performance. The study highlights a strong relationship between digital capabilities, organizational agility, strategic leadership, and superior employee performance. However, the main limitation of this research lies in its conceptual nature. Future studies are recommended to empirically test the model using quantitative methods such as Structural Equation Modeling (SEM) across various industry sectors, as well as conducting longitudinal studies to observe the long-term dynamics of digital capabilities and leadership.